Edukasi Konservasi Mangrove sebagai Upaya Peningkatan Kesadaran Lingkungan Masyarakat Pulau Pari - Novie Kurniasih Kamarudin; Naufal Ramadian; Jamil Latief; Muhamad Alimudin (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Mangrove ecosystems play an important role in maintaining the balance of coastal environments and sustaining the livelihoods of communities living in coastal areas. However, limited public awareness of the ecological functions and benefits of mangroves has repeatedly contributed to coastal environmental degradation. This community service program aimed to strengthen the environmental awareness of Pari Island residents, Thousand Islands, through a mangrove conservation education program. A participatory approach was employed by directly involving the community in various educational activities and conservation practices. The main activities included environmental outreach on the importance of mangrove ecosystems, group discussions on mangrove conservation efforts, and mangrove planting along the coastline. A total of 35 participants consisting of local residents, fishermen, and youth groups took part in this program. Evaluation was conducted through observation, interviews, and pre-test and post-test questionnaires to measure changes in participants' knowledge and awareness regarding mangrove conservation. The results demonstrated a measurable improvement in participants' understanding of mangrove functions and benefits following the education program. The program also encouraged community participation in coastal conservation efforts and fostered collective awareness of the importance of sustaining mangrove ecosystems. Community-based participatory education programs of this nature warrant serious consideration as a strategy for supporting sustainable mangrove conservation in coastal areas.